Development of Sustainable Concrete Utilizing Rice Husk Ash and Palm Oil Fuel Ash as Supplementary Cementitious Materials - Elliana Putri Anggraeni; Ahmad farhan; Riftya Sandy (Proceeding of the International Conferences on Engineering Sciences, 2025)
The construction industry in Indonesia faces challenges in finding sustainable materials for concrete production. This paper investigates the potential of rice husk ash (RHA) and palm oil fuel ash (POFA) as alternative supplementary cementitious materials (SCMs) in concrete. Both RHA and POFA are abundant agricultural by-products in Indonesia. Laboratory tests indicate that their incorporation enhances the compressive strength, durability, and sustainability of concrete. The findings highlight the dual benefit of reducing industrial waste and creating eco-friendly construction materials, thus contributing to the development of green infrastructure in Indonesia.